Re-assessing the Consistency of Sentencing Decisions in Cases of Assault: allowing for Within-Court Inconsistencies - Brunton-Smith, Ian (The British journal of criminology, 2020)
Empirical research has repeatedly focused on the potential existence of sentencing disparities. In particular, a growing number of studies have used multilevel models to quantify the extent that ‘similar’ offences are treated alike in different courts. This reliance on multilevel models has resulted in a natural focus on differences in the mean sentence awarded between courts, with the amount of within-group variability generally assumed to be the same in each court. In this paper, we show how multilevel models can be extended by allowing the magnitude of within-court differences to be different in each court. This provides a natural framework to connect between-court disparities with the sentencing differences that are thought to originate between judges operating within the same court, particularly in the absence of more fine-grained sentencing data about the judge residing in each case. Focusing specifically on cases of assault sentenced in 2011, we show that there are substantial differences in the range of sentences awarded in different courts, with the range almost twice as large in some courts. We also find that it is those courts that appear to show the traits of more homogeneous sentencing that sentence more harshly and that offences involving the presence of a weapon or evidence of good character and/or exemplary conduct were associated with higher levels of internal consistency.